Security Service Monitoring Using Face Recognition, Near Field Communication and Geolocation Technology - Eko Budi Setiawan; Rizky Milan Alpasya Wijaksono (Universitas Komputer Indonesia, 2025)
Security service companies require daily monitoring to ensure designated checkpoints are effectively supervised. This research aims to facilitate management in summarizing field reports and enhancing personnel supervision. A system was developed using Golang, JavaScript, Kotlin, and PostgreSQL, featuring a web application for administrators and a mobile application for field officers. The system integrates face recognition, GPS, location-based services, and NFC readers. Testing results demonstrated that the application functions according to the established workflow. Notably, the fastest face recognition detection time was 1.22 seconds. Additionally, RFID tags were successfully detected at distances under 4 cm with an average time of 0.378 seconds, while geolocation consistently provided accurate tracking.